Social Accountability 3.0: Engaging Citizens to Increase Systemic Responsiveness. Background Paper - Guerzovich, Florencia; Aston, Tom (Grupo Politeia, ESAG, UDESC and act4delivery, 2024)
Social accountability has become increasingly important to development programming since the 2004 World Development Report spearheaded its first generation of programming. In 2016, Thomas Carothers synthesized global experts’ perspectives on what became known as the second generation. With an evolving global context, new research and evaluations and tacit knowledge on how those assumptions played out in practice, the time is ripe for asking what the evidence since 2004 can tell us about what the social accountability’s next generation might look like? This meta-analysis takes stock of that knowledge through a systems lens and presents a possible “social accountability 3.0.” It draws on a database of 157 cases of initiatives implemented by different civil society organizations around the world and the lived experience of practitioners. Scholarly debates present practitioners’ options in binary terms, contrasting 1.0 minimalist and 2.0 maximalist options. The review finds that this binary is inaccurate and misleading; it masks practitioners’ diverse interpretations of 2.0 and range of feasibility considerations. Instead, work in the last decade looks more like a mosaic. By opening the analysis to the broader range of evidence, and reflecting more critically on scholars’ assumptions, a more adaptable middle path for social accountability 3.0 emerges. Its key outcomes include contributing to systemic responsiveness and an operational mechanism to rework the social contract.